Hubungan Antara Berpikir Positif dengan Efikasi Diri pada Mahasiswa Rantau di Yogyakarta dalam Menghadapi Dunia Kerja - Intan Munawaroh; Andhita Dyorita Kh (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Positive thinking is an individual's ability to see opportunities and solutions in difficult situations, which can enhance self-efficacy or confidence in one's abilities. For out-of-town students, this skill becomes crucial in facing academic and daily life challenges, especially in preparing to enter the workforce. High self-efficacy enables out-of-town students to face the demands of the job market with greater confidence and productivity. This study aims to examine the relationship between positive thinking and self-efficacy among out-of-town students in the Special Region of Yogyakarta in facing the workforce. The research subjects consisted of 100 out-of-town students, including 65 males and 35 females, aged 18-24 years. Data collection was conducted using research scales distributed through online surveys via Google Forms and social media. The data were analyzed using classical assumption tests and hypothesis testing. The results showed a significance value of 0.000, indicating a positive relationship between positive thinking and self-efficacy. However, the data did not meet the normality and linearity tests, requiring cautious interpretation of the findings. These results highlight the importance of positive thinking in enhancing the self-efficacy of out-of-town students, contributing to their readiness to face the workforce. This study recommends the development of programs to promote positive thinking as a strategy to strengthen the self-efficacy of out-of-town students. Future research is expected to address the limitations of classical assumption tests to produce more valid and generalizable findings.